Engineering the metal–organic interface by transferring a high-quality single layer graphene on top of organic materials. (June 2015) - Feng, Xuefei; Zhang, Liang; Ye, Yifan; Han, Yong; Xu, Qian; Kim, Ki-Jeong; Ihm, Kyuwook; Kim, Bongsoo; Bechtel, Hans; Martin, Michael; Guo, Jinghua; Zhu, Junfa
Abstract: We present a new method for transferring chemical vapor deposition (CVD)-grown graphene onto the surfaces of organic materials directly. Raman and near edge X-ray absorption fine structure measurements prove that high-quality and single layer graphene/organic thin films can be obtained with minimized impurity introduction. In-situ synchrotron radiation photoemission spectroscopy combined with ultraviolet photoelectron spectroscopy experiments demonstrate that the inserted graphene can not only act as a buffer layer to reduce the interfacial chemical reactions between the deposited Al and organic materials, but also tune the metal/organic interface electronic structure significantly. This new graphene transfer technique may have a great potential in the application of engineering the metal–organic interface properties, which is one of the key technologies for the optimal design and fabrication of organic electronic and optoelectronic devices.